Pengaruh Pengaruh Kinerja Keuangan, NPM dan EPS Terhadap Harga Wajar Saham Lembaga Pembiayaan di Bursa Efek Indonesia - Vivi Oktari; Maya Yuliani (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
The goal of this research is to examine the impact on the financial performance of the npm and eps listed on the Indonesia Stock Exchange (IDX). Earnings per share and profitability ratios (Net Profit Margin) are used to assess a company's performance. This study is quantitative in nature. Financial institution businesses that are listed on the IDX for the years 2018 through 2022 make up the research population. Purposive sampling is used in the sample selection method. Multiple linear regression is the data analysis strategy applied in this study. The results of the research shows that Variables Net Profit Margin (NPM), Return On Assets (ROA) and Earning Per Share (EPS) simultaneously and affect the level of stock prices